Deuterated Oxazoloisoindolinones via Photocatalytic Deoxygenative Cyclization of Amino Acid Derivatives - Wei, Chuanli; Geng, Yan; Ma, Yue; Yang, Hanlin; Yu, Songjie (Synlett, 2025)
A stereoselective synthesis of deuterated oxazoloisoindolinones using D2O was achieved through photocatalytic deoxygenation of readily available N-phthalimide amino acids, followed by an intramolecular 5-endo-trig cyclization. This protocol provides an efficient access to a broad array of deuterium-labeled N,O-heterobicycles with excellent deuterium incorporation.
Keywords: Amino acid; Photocatalytic deoxygenation; Cyclization; Deuterium incorporation; Oxazoloisoindolinone